Dynamics Formulation Of The Compilation Of Islamic Law And Role In Realizing Legal Certainty In Indonesian Religious Courts. - Hasan Munthe; Adrian Seputro Ginting (Program Pascasarjana UIN Sumatera Utara Medan, 2021)
This study aims to analyze the formulation process and reference sources of the Compilation of Islamic Law and its urgency in the development of Islamic civil law in Indonesia. The background of this study is based on the conditions before the birth of the Compilation of Islamic Law, which were characterized by the absence of uniform legal references in the religious courts, resulting in legal uncertainty due to differences in interpretation by judges who refer to various classical fiqh books. This study uses a normative juridical method with a historical and conceptual approach, through analysis of legal documents, fiqh literature, and jurisprudence practices. The results show that the Compilation of Islamic Law is a product of collective ijtihad formulated through systematic stages, including the study of fiqh books, interviews with scholars, jurisprudence analysis, and comparative studies with Muslim countries. The reference sources of the Compilation of Islamic Law include the Qur'an, Hadith, ijma', qiyas, and various fiqh books from different schools of thought, which are then contextualized with the social conditions of Indonesian society. The presence of the KHI (Compilation of Islamic Law) plays a significant role in achieving legal unification and certainty in religious courts, while also serving as a codification of Islamic law that adapts to the national legal system. Thus, the KHI serves not only as a normative guideline but also as a crucial instrument for harmonizing sharia values and positive law in Indonesia.